The Effect of Earning Per Share and Return on Investment on the Share Price of PT Astra Otoparts Tbk (2012-2021 Period) - Maolani Paij Watiningsih; Prista Tarigan (Journal of Accounting and Finance Management, 2021)
Financial reports are a form of information published by companies to meet the needs of investors that describe how much the company's wealth, income earned by the company, as well as information about the company's achievements. Apart from being information for investors, financial reports can also be a reference for companies to make decisions and predict what will happen in the future. After having information in the form of financial reports, the next activity is to evaluate the company's performance, namely by analyzing financial statements. This activity is carried out by analyzing financial ratios. In general, financial ratios are analytical activities carried out with the aim of describing a comparison between the values ??of the components in the financial statements. Financial ratios are divided into several ratios, namely, liquidity ratios, solvency ratios, activity ratios and profitability ratios. Of the four ratios, researchers use a profitability ratio where the ratio is closely related to all investment activities and the ratio shows that the greater the value of the ratio, the better the company's ability to earn profits. In this ratio, there is one ratio, namely Return on Investment (ROI), which is the ratio used to calculate the value of an investment. For example, investors want to know the potential ROI of an investment before providing any funds to a company. Another factor in measuring the soundness of a company apart from financial ratios is by looking at stock prices.